Potential study of water extraction from selected plants - Musa, S.; Abu Mansor, N.A. A.; Bujang, S. S.; Mohd Kamil, N. A. F.; Adnan, M. S.; Hamdan, R. (EDP Sciences, 2017)
Water is absorbed by the roots of a plant and transported subsequently as a liquid to all parts of the plant before being released into the atmosphere as transpiration. In this study, seven(7)selected plant species collected from urban, rural and forested areas were studied and characterized. The water was collected using transparent plastic bag that being tied to the tree branches. Then, the vapouris water trapped inside the plastic bag and through the condensation process, it become water droplets. Water quality parameters such as temperature, pH value, DO, turbidity, colour, magnesium, calcium, nitrate and chloride were analyzed. The analysis was compared to drinking water quality standard set by the Ministry of Health Malaysia. Based on the results, it shows that banana leaf has a higher rate of water extraction compared to others. Thus, the plant can be categorised as a helpful guide for emergency use of water or as an alternative source to survival.